Structural Change in West Africa : A Tale of Gain and Loss - Haile, Fiseha (World Bank, Washington, DC, 2018)
Economic growth in Benin, Burkina Faso, and Cote d'Ivoire occurred in tandem with a rapid exodus of labor out of agriculture. This paper investigates the contribution (or lack thereof) of within- and between-sector productivity changes to overall productivity growth and output per capita growth since 2000. Productivity growth was relatively significant in Burkina Faso, modest in Benin, and in the negative territory in Cote d'Ivoire. The results show that static structural change drove growth in Burkina Faso and Benin, although it was partly offset by a dynamic loss in Benin. However, structural change made a smaller contribution in Cote d'Ivoire. Within-sector productivity loss generally held back growth. The pattern of structural change observed in Benin, Burkina Faso, and Cote d'Ivoire starkly contrasts with that of Asia, where within-sector productivity gains were preponderant and dynamic structural change was the norm rather than the exception. The bulk of Benin, Burkina Faso, and Cote d'Ivoire's displaced agricultural workers moved into still-low productivity service activities, as is typical of the African sample.